Clinical forms of apraxia in patients with Alzheimer’s disease - Popović, Emina; Pavlovic, Dragan; Milikić, Bojana; Popović, Jovan; Stojanović, Jasmina (Specijalna edukacija i rehabilitacija, 2023)
Clinical forms of apraxia in patients with Alzheimer’s disease Emina D. Popovića,b, Dragan M. Pavlovićc, Bojana B. Milikića, Jovan D. Popovićd,e, Jasmina D.Stojanovića,f aUniversity of Kragujevac – Faculty of Medical Sciences, Kragujevac, Serbia bHealth center Petrovac na Mlavi - Children’s department, Petrovac na Mlavi, Serbia cPolyclinic Antamedica, Belgrade, Srbija dUniversity of Belgrade - Faculty of Veterinary Medicine, Belgrade, Serbia eInstitute of Veterinary Specialists „Požarevac“, Požarevac, Serbiaf fUniversity Clinical Center of Kragujevac - Otorhinolaryngology Clinic, Kragujevac, Serbia Introduction. Alzheimer’s disease is the most common form of dementia. Apraxia can be one of the symptoms of Alzheimer’s disease. Apraxia is defined as an acquired deficit in the execution of movements that cannot be explained by motor or sensory impairments. Aim. The main aim of this research is to determine the types of apraxia in people with Alzheimer’s dementia and to point out the importance of early rehabilitation of these patients. Method. The sample consists of 15 patients with Alzheimer’s dementia (amnestic type - multiple domains) aged from 50 to 85 years. In addition to the free interview, which follows predetermined principles, a neurological clinical assessment of motor skills and sensitivity and a neurobehavioral assessment of appearance, behavior, and emotions were conducted. The examination was conducted according to the established criteria at the Antamedica Polyclinic in Belgrade. Results. The results of our study show that patients with Alzheimer’s disease are impaired in both the first and second stages: time orientation, attention, arithmetic, remembering, naming, writing, and copying figures. On the other hand, other cognitive functions are relatively well preserved in these stages of the disease. Patients with Alzheimer’s disease have an impaired ability to understand spoken and written language. In contrast, no deficits were found on the verbal-visual discrimination test. Conclusion. Assessment of apraxia has become an important aspect of neurodegenerative diseases and a main indicator for psychotherapy and occupational therapy, contributing to the quality of life of the elderly, primarily with cognitive decline.